Proteome-transcriptome analysis and proteome remodeling in mouse lens epithelium and fibers. (February 2019) - Zhao, Yilin; Wilmarth, Phillip A.; Cheng, Catherine; Limi, Saima; Fowler, Velia M.; Zheng, Deyou; David, Larry L.; Cvekl, Ales
Abstract: Epithelial cells and differentiated fiber cells represent distinct compartments in the ocular lens. While previous studies have revealed proteins that are preferentially expressed in epithelial vs. fiber cells, a comprehensive proteomics library comparing the molecular compositions of epithelial vs. fiber cells is essential for understanding lens formation, function, disease and regenerative potential, and for efficient differentiation of pluripotent stem cells for modeling of lens development and pathology in vitro . To compare protein compositions between the lens epithelium and fibers, we employed tandem mass spectrometry (2D-LC/MS) analysis of microdissected mouse P0.5 lenses. Functional classifications of the top 525 identified proteins into gene ontology categories by molecular processes and subcellular localizations, were adapted for the lens. Expression levels of both epithelial and fiber proteomes were compared with whole lens proteome and mRNA levels using E14.5, E16.5, E18.5, and P0.5 RNA-Seq data sets. During this developmental time window, multiple complex biosynthetic and catabolic processes generate the molecular and structural foundation for lens transparency. As expected, crystallins showed a high correlation between their mRNA and protein levels. Comprehensive data analysis confirmed and/or predicted roles for transcription factors (TFs), RNA-binding proteins (e.g. Carhsp1), translational apparatus including ribosomal heterogeneity and initiation factors, microtubules, cytoskeletal [e.g. non-muscle myosin IIA heavy chain (Myh9) and βB2-spectrin (Sptbn2)] and membrane proteins in lens formation and maturation. Our data highlighted many proteins with unknown functions in the lens that were preferentially enriched in epithelium or fibers, setting the stage for future studies to further dissect the roles of these proteins in fiber cell differentiation vs. epithelial cell maintenance. In conclusion, the present proteomic datasets represent the first mouse lens epithelium and fiber cell proteomes, establish comparative analyses of protein and RNA-Seq data, and characterize the major proteome remodeling required to form the mature lens fiber cells. Highlights: First comparative analysis of mouse lens proteomes and transcriptomes. Reveals quantitative differences in proteins found in lens epithelium and lens fibers. Identifies fiber cell enriched protein components of the translational system. Evidence for proteome remodeling in differentiating lens fiber cells. Data source for prioritizing protein candidates for functional studies.